ANALISIS USAHA DAN STRATEGI PENGEMBANGAN AGRIBISNIS BUAH NAGA CV. KUSUMO WANADRI KULONPROGO - Rika Fitri Ilvira; Any Suryantini; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
The objective of this research are to determine the feasibility of dragon fruit agribusiness (seeding, cultivation, and processing) and formulates strategies of agribusiness development in Kulon Progo regency. The method in this research is to used descriptive analysis. The analyzed data are forming performance of factors internal and external strategic agribusiness. The location is determined (purposive) at CV. Kusuma Wanadri located in Bebekan Village, Glagah Indah, Temon district with considerating of the company doing all the dragon fruit agribusiness activities (seeding, cultivation, and processing). The analysis tools are: analysis of income, BEP analysis, B/C Ratio, payback period and SWOT analysis.Result of feasibility analysis showed that the activity seeding and processing is feasible to be developed in Kulon Progo. Revenue of seeding activities Rp 981.550.128, value of production BEP is 756 stem, and price BEP is Rp 918 per stem, the value of B/C ratio is 37,11 and the payback period is 0.002 month. Revenue of cultivating activities Rp 7.491.123,516 the value of production BEP is 73.035 kg and price BEP is Rp 4.864 per kg, the value of B/C ratio is 4,13 and a payback period of 0,18 year. Revenue of processing activities Rp 14.787.634, value of production BEP is 3.542 glass, price BEP is Rp 2.725 per glass, the value of B/C ratio is 0,83 and payback period is 0,03 month.Strategy that is suitable for seeding is S-O (Strengths – Opportunities), S-T (Strengths-Treaths) for cultivation activities and strategies W-O (Weakness-Opportunities) for dragon fruit processing activities.